a) 5*8-(9*0+64:8)+109= ;(6*11+147)+50:5= ; b) 81:9*6+(831-8*10)= ; (77-69)*6+45:5+4*8= .
Răspunsuri la întrebare
Răspuns de
6
Răspuns:
Explicație pas cu pas:
5*8-(9*0+64:8)+109=40-(0+8)+109=40-8+109=32+109=141
(6*11+147)+50:5=(66+147)+10=213+10=223
81:9*6+(831-8*10)=9*6+(831-80)=54+751=805
(77-69)*6+45:5+4*8=8*6+9+32=48+9+32=57+32=89
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă